900-mW high brightness buried ridge lasers by selective area epitaxy - Swint, R.B.; Huber, A.E.; Yeoh, T.S.; Woo, C.Y.; Coleman, J.J.; Faircloth, B.O.; Zediker, M.S. (IEEE photonics technology letters, 2002)
A study has been made of high power single lateral mode buried ridge lasers fabricated by selective area epitaxy. Several ridge thicknesses have been evaluated simultaneously in a single fabrication run. These lasers operate purely in the fundamental mode to output powers in excess of 450 mW, after which they are subject to beam steering or higher order mode operation. For weakly guided lasers, the output remains in a narrow lobe [full-width at half-maximum (FWHM)] = 4/spl deg/-6/spl deg/, stable at a given current value, up to output powers of 900 mW in CW tests.